Projeto e desenvolvimento de um inversor solar ponte completa bidirecional para microrredes CC conectadas à rede CA em baixa tensão - Pires, Lucas Pereira (2016)
This work presents the proposal and analysis of a Bidirectional Full-Bridge Inverter (BFBI) applied to DC (direct current) microgrids in terms to its performance in active power injection into the AC (alternating current) grid and DC bus voltage regulation front of the inherent intermittences observed in photovoltaic generators, which should not cause disturbances in the dc loads. The digital control strategy is implemented from a DSP (Digital Signal Processor) with Proportional Resonant (P + Res) controller combined with 3th, 5th and 7th Harmonic Correction in the current imposed on the grid for the two modes of operation, which enables the adjustment in power quality to IEEE 1547 (injection) and IEC 61.000-3-2 (rectification) international standards. Finally, this work present the qualitative and quantitative analysis of the proposed system, still containing the design specifications, simulation and experimental results obtained with the construction of a 2.2 kWp prototype.